Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Matematika Siswa Smp Negeri 1 Rantau Selatan - Siregar, Khofifah Indriyan; Harahap, Amin; Hasibuan, Lily Rohanita (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to investigate the effectiveness of the Problem Based Learning approach in overcoming mathematics learning difficulties in high school students The approach in this study uses a quantitative method through quasi-experimental experiments. The research participants consisted of 65 individuals who were samples from class VII SMP NEGERI 1 RANTAU SELATAN in the 2023–2024 academic year. It consists of four classes: two classes VII A, B, and two classes VII C, then there is There were interviews with participants from classes VII A and VII B, students were divided into two groups: an experimental group that used the PBL approach and a control group that used conventional learning methodsData were collected through math tests given before and after treatment. Data analysis was carried out using a t-test to measure the difference in pretest and post test scores between the two groups.